Biochar microtube interconnected hydrotalcite nanosheets for the adsorption of aqueous Sb(III). (2nd July 2022) - Zhang, Xinyue; Xie, Nianyi; Guo, Ying; Guo, Rongxiu; Jiang, Tong; Wang, Yao; Wang, Yiming; Niu, Dun; Qi, Yang; Sun, Hong-bin
Abstract: Actuated by the non-ionic heavy metal of antimony (Sb) contaminants with undesired toxicity to the environment and human health, capturing Sb is urgent to remedy contaminated water. Herein, the lamellar MnCo hydrotalcite was grown on catkin-derived biochar through the in situ etching of ZIF-L to construct a hierarchical microtube@nanosheet hybrid (CLMH) for Sb immobilization. The adsorption behaviour and mechanism of trivalent antimony (Sb (III)) on the CLMH were investigated. The CLMH shows good pH applicability for capturing Sb(III) at pH from 2 to 9. The excellent adsorption capacity of CLMH for Sb(III) is 247.62 mg g −1 at 303 K, and the endothermic process is proved by the positive value of Δ H 0 (10.54 kJ mol −1 ). The adsorption process is fitted with the intra-particle diffusion model, which can be described with external mass transfer, intraparticle diffusion in pores, and equilibrium stage. The adsorption mechanism is proved, which includes the bind of Metal–O–Sb bonds by inner-sphere complex, the embedding of Sb in the intercalation of hydrotalcite, redox between Mn and Sb, and functional groups dependent anchoring effect. The work benefits the understanding of the antimony removal behaviour over the hierarchical microtube@nanosheet hybrids.